Stimulation of abdominal and upper thoracic muscles with surface electrodes for respiration and cough: Acute studies in adult canines. (4th May 2018) - Walter, James S.; Posluszny, Joseph; Dieter, Raymond; Dieter, Robert S.; Sayers, Scott; Iamsakul, Kiratipath; Staunton, Christine; Thomas, Donald; Rabbat, Mark; Singh, Sanjay
Abstract : Objective : To optimize maximal respiratory responses with surface stimulation over abdominal and upper thorax muscles and using a 12-Channel Neuroprosthetic Platform. Methods : Following instrumentation, six anesthetized adult canines were hyperventilated sufficiently to produce respiratory apnea. Six abdominal tests optimized electrode arrangements and stimulation parameters using bipolar sets of 4.5 cm square electrodes. Tests in the upper thorax optimized electrode locations, and forelimb moment was limited to slight-to-moderate. During combined muscle stimulation tests, the upper thoracic was followed immediately by abdominal stimulation. Finally, a model of glottal closure for cough was conducted with the goal of increased peak expiratory flow. Results : Optimized stimulation of abdominal muscles included three sets of bilateral surface electrodes located 4.5 cm dorsal to the lateral line and from the 8 th intercostal space to caudal to the 13 th rib, 80 or 100 mA current, and 50 Hz stimulation frequency. The maximal expired volume was 343 ± 23 ml (n=3). Optimized upper thorax stimulation included a single bilateral set of electrodes located over the 2 nd interspace, 60 to 80 mA, and 50 Hz. The maximal inspired volume was 304 ± 54 ml (n=4). Sequential stimulation of the two muscles increased the volume to 600 ± 152 ml (n=2), and the glottal closure maneuver increased the flow. Conclusions : Studies in an adult canine model identified optimal surface stimulation methods for upper thorax and abdominal muscles to induce sufficient volumes for ventilation and cough. Further study with this neuroprosthetic platform is warranted.